2015
DOI: 10.1039/c5ra05438a
|View full text |Cite
|
Sign up to set email alerts
|

Significantly improved de/rehydrogenation properties of lithium borohydride modified with hexagonal boron nitride

Abstract: The remarkable hydrogen de/absorption properties of lithium borohydride are achieved by mechanically milling LiBH 4 with hexagonal boron nitride (h-BN). It is found that the dehydrogenation properties of LiBH 4 are improved with increasing the amount of h-BN. The 30 mol% h-BN doped LiBH 4 composite starts to release hydrogen from just 180 C, which is 100 C lower than the onset dehydrogenation temperature of ball milled LiBH 4 . Moreover, the 30 mol% h-BN doped LiBH 4 composite can release 12.6 wt% hydrogen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…To further study the desorption kinetics of the LiBH 4 –20 wt% y composites (y = Fe 3 O 4 , rGO, and Fe 3 O 4 @rGO), DSC tests at different heating rates were performed to evaluate the activation energy ( E a ) of these composites using Kissinger’s method: 38 …”
Section: Resultsmentioning
confidence: 99%
“…To further study the desorption kinetics of the LiBH 4 –20 wt% y composites (y = Fe 3 O 4 , rGO, and Fe 3 O 4 @rGO), DSC tests at different heating rates were performed to evaluate the activation energy ( E a ) of these composites using Kissinger’s method: 38 …”
Section: Resultsmentioning
confidence: 99%
“…The remarkable hydrogen de/absorption properties were also achieved in the milled LiBH 4 /h-BN composites [18,19]. The 30 mol % h-BN doped LiBH 4 composite started to release hydrogen from 180 • C, which was 100 • C lower than the onset hydrogen desorption temperature of ball-milled LiBH 4 [18]. For the 75 mol % h-BN doped LiBH 4 composite, the on-set desorption temperature of LiBH 4 was reduced to 175 • C and the peak desorption temperature was reduced by 80 • C compared with milled LiBH 4 [19].…”
Section: Introductionmentioning
confidence: 83%
“…For instance, NH 3 BH 3 /h-BN composite released hydrogen at low temperature with minimum induction time and less exothermicity [17]. The remarkable hydrogen de/absorption properties were also achieved in the milled LiBH 4 /h-BN composites [18,19]. The 30 mol % h-BN doped LiBH 4 composite started to release hydrogen from 180 • C, which was 100 • C lower than the onset hydrogen desorption temperature of ball-milled LiBH 4 [18].…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that hexagonal boron nitride (h-BN) additive greatly improves the dehydrogenation of LiBH4. 95 Sodium borohydride (NaBH4) is an excellent hydrogen storage material, but its application is restricted by irreversibility of hydrolysis and high cost of regeneration. To regenerate NaBH4 with high yield and low costs, the hydrolytic product NaBO2 reacts with CO2, forming Na2B4O7•10H2O and Na2CO3, both of which are ball-milled with Mg under ambient conditions to form NaBH4 in high yield (close to 80%).…”
Section: Figure 8 Activation Energies Of H2 Sorption and Dehydrogenat...mentioning
confidence: 99%